Class I and II Histone Deacetylase Inhibition by ITF2357 Reduces SLE Pathogenesis In Vivo - Regna, Nicole L. (2014)
We sought to determine if a specific class I and II HDAC inhibitor (ITF2357) was able to decrease disease in lupus-prone NZB/W mice through regulation of T cell profiles. From 22 - 38 weeks-of-age, NZB/W and non-lupus NZW mice were treated with ITF2357 (5 mg/kg or 10 mg/kg), or vehicle control. Body weight and proteinuria were measured every 2 weeks, while sera anti-dsDNA and cytokine levels were measured every 4 weeks. Kidney disease was determined by sera IgG levels, immune complex deposition, and renal pathology. T lymphocyte profiles were assessed using flow cytometric analyses. Our results showed NZB/W mice treated with the high-dose of ITF2357 had decreased renal disease and inflammatory cytokines in the sera. Treatment with ITF2357 decreased the Th17 phenotype while increasing the percentage of Tregs as well as Foxp3 acetylation. These results suggest that specific HDAC inhibition may decrease disease by altering T cell differentiation and acetylation.